Chronic phosphocreatine depletion by the creatine analogue beta-guanidinopropionate is associated with increased mortality and loss of ATP in rats after myocardial infarction. - Horn, M; Remkes, H; Strömer, H; Dienesch, C; Neubauer, S (2001)
BACKGROUND: The failing myocardium is characterized by reductions of phosphocreatine (PCr) and free creatine content and by decreases of energy reserve via creatine kinase (CK), ie, CK reaction velocity (Flux(CK)). It has remained unclear whether these changes contribute directly to contractile dysfunction. In the present study, myocardial PCr stores in a heart failure model were further depleted by feeding of the PCr analogue beta-guanidinopropionate (GP). Functional and metabolic consequences were studied. METHODS AND RESULTS: Rats were subjected to sham operation or left coronary artery ligation (MI). Surviving rats were assigned to 4 groups and fed with 0% (n=7, Sham; n=5, MI) or 1% (n=7 Sham+GP, n=8 MI+GP) GP. Two additional groups were fed GP for 2 or 4 weeks before MI. After 8 weeks, hearts were isolated and perfused, and left ventricular pressure-volume curves were obtained. High-energy phosphate metabolism was determined with (31)P NMR spectroscopy. After GP feeding or MI, left ventricular pressure-volume curves were depressed by 33% and 32%, respectively, but GP feeding in MI hearts did not further impair mechanical function. Both MI and GP feeding reduced PCr content and Flux(CK), but here, effects were additive. In MI+GP rats, PCr levels and Flux(CK) were reduced by 87% and 94%, respectively. Although ATP levels were maintained in the GP and MI groups, ATP content was reduced by 18% in MI+GP hearts. Furthermore, 24-hour mortality in GP-prefed rats was 100%. CONCLUSIONS: Rats with an 87% predepletion of myocardial PCr content cannot survive an acute MI. Chronically infarcted hearts subjected to additional PCr depletion cannot maintain ATP homeostasis.